Design and characterization of Chitin- Glucan polymeric structures for wound dressing materials - Ardiyanti, Rizza (2014)
The main objective of this work was the development of polymeric structures, gel and films, generated from the dissolution of the Chitin-Glucan Complex (CGC) in biocompatible ionic liquids for biomedical applications. Similar as chitin, CGC is only soluble in some special solvents which are toxic and corrosive. Due to this fact and the urgent development of biomedical applications, the need to use biocompatible ionic liquids to dissolve the CGC is indispensable. For the dissolution of CGC, the biocompatible ionic liquid used was Choline acetate. Two different CGC’s, KiOnutrime from KitoZyme and biologically produced CGC from Faculdade de Ciencias e Tecnologia (FCT) - Universidade Nova de Lisboa, were characterized in order to develop biocompatible wound dressing materials. The similar result is shown in term of the ratio of chitin:glucan, which is 1:1.72 for CGC-FCT and 1:1.69 for CGC-Commercial. For the analysis of metal element content, water and inorganic salts content and protein content, both polymers showed some discrepancies, where the content in CGC-FCT is always higher compared to the commercial one. The different characterization results between CGC-FCT and CGC-Commercial could be addressed to differences in the purification method, and the difference of its original strain yeast, whereas CGC-FCT is derived from P.pastoris and the commercial CGC is from A.niger. This work also investigated the effect of biopolymers, temperature dissolution, non-solvent composition on the characteristics of generated polymeric structure with biocompatible ionic liquid. The films were prepared by casting a polymer mixture, immersion in a non-solvent, followed by drying at ambient temperature. Three different non-solvents were tested in phase inversion method, i.e. water, methanol, and glycerol. The results indicate that the composition of non-solvent in the coagulation bath has great influence in generated polymeric structure. Water was found to be the best coagulant for producing a CGC polymeric film structure. The characterizations that have been done include the analysis of viscosity and viscoelasticity measurement, as well as sugar composition in the membrane and total sugar that was released during the phase inversion method. The rheology test showed that both polymer mixtures exhibit a non- Newtonian shear thinning behaviour. Where the viscosity and viscoelasticity test reveal that CGCFCT mixture has a typical behaviour of a viscous solution with entangled polymer chains and CGCCommercial mixture has true gel behaviour. The experimental results show us that the generated CGC solution from choline acetate could be used to develop both polymeric film structure and gel. The generated structures are thermally stable at 100° C, and are hydrophilic. The produced films have dense structure and mechanical stabilities against puncture up to 60 kPa.